Sinergisme Isolat Potensial Biofertilizer Bacillus cereus yang Dikonsorsiumkan - Muhammad Fajar; Siti Khotimah; Rahmawati Rahmawati (Universitas Negeri Semarang, 2023)
A consortium of microorganisms is a mixture of microbial populations in the form of a community that has cooperative, commensal, and mutualistic relationships. Naturally, bacteria are able to communicate with each other. The relationship between bacteria can have a synergistic relationship if the substrate is sufficient and the bacteria do not inhibit each other's growth. In this study, Bacillus cereus isolates SP1, SP2, and SP3 isolated from Sungai Ambawang peatland, Kubu Raya Regency, West Kalimantan will be consorted. The purpose of this study was to determine the synergism of three strains of Bacillus cereus bacteria. All isolates tested for synergism against other isolates showed no inhibition zone at the intersection between isolates. This means that each isolate can synergize with one another. The synergism test results show that three strains of Bacillus cereus bacteria can synergize in the manufacture of biofertilizers.